Microglia and infiltrating macrophages in ictogenesis and epileptogenesis - Bröer, Sonja; Pauletti, Alberto (Frontiers in Molecular Neuroscience, 2024)
Phagocytes maintain homeostasis in a healthy brain. Upon injury, they are essential for repairing damaged tissue, recruiting other immune cells, and releasing cytokines as the first line of defense. However, there seems to be a delicate balance between the beneficial and detrimental effects of their activation in a seizing brain. Blocking the immigration of peripheral phagocytes (macrophages) or their depletion can partially alleviate epileptic seizures and prevent the death of neurons in experimental models of epilepsy. However, the depletion of resident phagocytes in the brain (microglia) can aggravate disease outcomes. This review describes the role of resident microglia and peripheral infiltrating monocytes in animal models of acutely triggered seizures and epilepsy. Understanding the roles of phagocytes in ictogenesis and the time course of their activation and involvement in epileptogenesis and disease progression can offer us new biomarkers to identify patients at risk of developing epilepsy after a brain insult, as well as provide novel therapeutic targets for treating epilepsy.